Application of graphene-based materials in developing sustainable infrastructure: An overview - Asim N.; Badiei M.; Samsudin N.A.; Mohammad M.; Razali H.; Soltani S.; Amin N. (Elsevier Ltd, 2023)
Building materials; Buildings; Chemical modification; Construction; Construction industry; Corrosion resistance; Corrosion resistant coatings; Energy utilization; Environmental technology; Graphene; Sustainable development; Building and construction; Buildings materials; Mechanical characteristics; Mechanical/physical properties; Mechanical/thermal properties; Modification; Nano additives; Performance; Physical characteristics; Sustainable infrastructure; Durability